2019
DOI: 10.3897/natureconservation.34.27610
|View full text |Cite
|
Sign up to set email alerts
|

Benthic studies in LTER sites: the use of taxonomy surrogates in the detection of long-term changes in lagoonal benthic assemblages

Abstract: In benthic studies, the identification of organisms at the species level is known to be the best source for ecological and biological information even if time-consuming and expensive. However, taxonomic sufficiency (TS) has been proposed as a short-cut method for quantifying changes in biological assemblages in environmental monitoring. In this paper, we set out to determine whether and how the taxonomic complexity of a benthic assemblage influences the results of TS at two different long-term ecological resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…For soft-bottom macrofauna, commonly used to assess anthropogenic impacts or environmental changes in coastal marine ecosystems, the relevance of taxonomic surrogacy to address changes in community composition and structure has already been evaluated, frequently over gradients of pollution or disturbances (Olsgard & Somerfield 2000, Kokesh et al 2022. However, most studies used the highertaxon method rather than other surrogates (Bevilacqua et al 2012), and scarcely in the context of longterm monitoring (but see Pitacco et al 2019). The few studies focusing on long-term series relied on methods not explicitly designed for temporal dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For soft-bottom macrofauna, commonly used to assess anthropogenic impacts or environmental changes in coastal marine ecosystems, the relevance of taxonomic surrogacy to address changes in community composition and structure has already been evaluated, frequently over gradients of pollution or disturbances (Olsgard & Somerfield 2000, Kokesh et al 2022. However, most studies used the highertaxon method rather than other surrogates (Bevilacqua et al 2012), and scarcely in the context of longterm monitoring (but see Pitacco et al 2019). The few studies focusing on long-term series relied on methods not explicitly designed for temporal dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Terlizzi et al, 2009;Aguado-Gimeńez et al, 2015;Xiong et al, 2018). Some studies on environmental stress responses have shown that responses to environmental factors at the family or genus level are similar to that at the species level (Landeiro et al, 2012;Pitacco et al, 2019a). Many studies have concluded that the identification of organisms at the genus and family levels is sufficient (Chessman et al, 2009;Dauvin et al, 2016;Pitacco et al, 2019b), and one study even concluded that environmental quality assessments conducted at the family and genus levels are more accurate than those at conducted the species level (Checon and Amaral, 2017).…”
mentioning
confidence: 99%
“…The long-term analysis of various ecosystem components has also proved to be useful to identify key variables that may allow environmental dynamics to be followed in view of possible future limitations of sampling or analytical efforts. This is the case of tintinnids for marine microzooplankton (Monti-Birkenmeier et al 2019), taxonomic surrogates for benthic assemblages in transitional ecosystems (Pitacco et al 2019) and nutrients, such as nitrites and reactive phosphorus for the trophic status of the Venice Lagoon (Sfriso et al 2019). The value of LTER investigations, generally conducted at a single site, is further enhanced by expanding the spatial scale of the observations in a comparative effort, which is especially useful for the prediction of future changes in marine systems in response to climate variability and ocean warming (Kröncke et al 2019).…”
mentioning
confidence: 99%